1980
DOI: 10.2307/279865
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Test of the Effects of Heat Treatment of Flakeable Stone

Abstract: Widely held notions about the effects of heat treatment of flakeable stone were tested by agitating matching sets of regularly shaped pieces of heated and raw chert. The tests indicate that heat treatment changes some of the variables that control flake formation although not necessarily in ways that make flintworking "easier." It appears that in order to realize an advantage to the practice, the flintknapper must call on individual skill to make technical readjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 4 publications
0
20
0
4
Order By: Relevance
“…Increased consistency of fracture is associated with longer flake removals, fewer step and hinge terminations, and the production of sharper edges (Bleed and Meier, 1980;Crabtree and Butler, 1964;Domanski et al, 1992). Toolkits made on materials that fracture predictably are thought to be easier to design because fracture is easier to control (Luedtke, 1992).…”
Section: Fracture Predictabilitymentioning
confidence: 98%
“…Increased consistency of fracture is associated with longer flake removals, fewer step and hinge terminations, and the production of sharper edges (Bleed and Meier, 1980;Crabtree and Butler, 1964;Domanski et al, 1992). Toolkits made on materials that fracture predictably are thought to be easier to design because fracture is easier to control (Luedtke, 1992).…”
Section: Fracture Predictabilitymentioning
confidence: 98%
“…The thicker pieces do not heat or cool evenly and, as a result, crack or craze rather easily'' (Crabtree and Butler, 1964, p. 2). Many experimental programs have sought to define the optimum temperature and length of time required to heat treat siliceous rocks, and observed that these varied between different materials, but these conclusions have not quantified how heating must be varied with specimen size if thermal fracture is to be avoided (Mandeville, 1973;Rick and Chappell, 1983;Bleed and Meier, 1980;Purdy, 1974;Schindler et al, 1982). We tested the effects that altering size had on the temperature at which a raw material fractured.…”
Section: Framing Experimental Investigations Into the Process Of Heatmentioning
confidence: 98%
“…Dichos cambios tienen distintos efectos. La mejora más evidente es la necesidad de una menor fuerza del tallador en el momento de fracturar la roca (Crabtree y Butler 1964;Bleed y Meier 1980). Según Ahler (1983, cit.…”
Section: El Tratamiento Térmicounclassified
“…El tratamiento térmico es una ventaja en el momento de obtener productos de mayor longitud (Rick 1978;Bleed y Meier 1980). Mejora considerablemente la efi cacia de la talla por presión y también la percusión mediante percutor blando y la percusión indirecta.…”
Section: El Tratamiento Térmicounclassified